Contribution à l'étude des boues de la station d'épuration des eaux usées de la ville de Ouargla - BAAISSA, Fatima; BELMEKKI, Zohra; BEN AISSA, Hana (Université of Eloued, 2022)
Our work concerns the physico-chemical and bacteriological characterization of the sludge from the sludge from the Ouargla wastewater treatment plant in terms of pH, EC, dryness fertilizing elements (N, P, K, Mg), volatile matter in suspension totale and faecal coliforms and fecal streptococci. The results obtained show that this sludge characterized by a very high dryness which was estimated at 95% approximately average suspended volatile matter, alkalinity and salinity, the presence of nitrogen, phosphorus, potassium and magnesium as fertilizing elements, contamination by total coliforms and the absence of faecal coliforms and faecal streptococci.
Biodiversité et environnement
Keywords: sludge; ouargla; physico-chemical and bacteriological characterization; fertilizing elements.; الحمأة; معالجة المياه